GUBIC: The global urban biological invasions compendium for plants - Daijiang Li; Luke J. Potgieter; Myla F. J. Aronson; Irena Axmanová; Benjamin Baiser; Marta Carboni; Laura Celesti‐Grapow; Sonja Knapp; Ingolf Kühn; Ana Carolina Lacerda de Matos; Zdeňka Lososová; Flavia A. Montaño‐Centellas; et al. (Ecological Solutions and Evidence)
Abstract Urban areas are foci for the introduction of non‐native plant species, and they often act as launching sites for invasions into the wider environment. Although interest in biological invasions in urban areas is growing rapidly, and the extent and complexity of problems associated with invasions in these systems have increased, data on the composition and numbers of non‐native plants in urbanized areas remain scattered and idiosyncratic. We assembled data from multiple sources to create the Global Urban Biological Invasions Compendium (GUBIC) for vascular plants representing 553 urban centres from 61 countries across every continent except Antarctica. The GUBIC repository includes 8140 non‐native plant species from 253 families. The number of urban centres in which these non‐native species occurred had a log‐normal distribution, with 65.2% of non‐native species occurring in fewer than 10 urban centres. Practical implications: The dataset has wider applications for urban ecology, invasion biology, macroecology, conservation, urban planning and sustainability. We hope this dataset will stimulate future research in invasion ecology related to the diversity and distributional patterns of non‐native flora across urban centres worldwide. Further, this information should aid the early detection and risk assessment of potential invasive species, inform policy development and assist in setting management priorities.